Emerging materials to prepare mixed matrix membranes for pollutant removal in water - Lim, Yu Jie (2022)
Various pollutants of different sizes are directly (e.g., water-borne diseases) and indirectly (e.g., accumulation via trophic transfer) threatening our water health and safety. To cope with this matter, multifaceted approaches are required for advanced wastewater treatment more efficiently. Wastewater treatment using mixed matrix membranes (MMMs) could provide an excellent alternative since it could play two roles in pollutant removal by covering adsorption and size exclusion of water contaminants simultaneously. This paper provides an overview of the research progresses and trends on the emerging materials used to prepare MMMs for pollutant removal from water in the recent five years. The transition of the research trend was investigated, and the most preferred materials to prepare MMMs were weighed up based on the research trend. Various application examples where each emerging material was used have been introduced along with specific mechanisms underlying how the better performance was realized. Lastly, the perspective section addresses how to further improve the removal efficiency of pollutants in an aqueous phase, where we could find a niche to spot new materials to develop environmentally friendly MMMs, and where we could further apply MMMs.